Primary bone microanatomy records developmental aspects of life history in catarrhine primates. Issue 92 (March 2016) - McFarlin, Shannon C.; Terranova, Carl J.; Zihlman, Adrienne L.; Bromage, Timothy G.
Abstract: A central challenge in human origins research is to understand how evolution has shaped modern human life history. As fossilized remains of our ancestors provide the only direct evidence for life history evolution, efforts to reconstruct life history in paleontological contexts have focused on hard tissues, particularly on dental development. However, among investigators of other vertebrate groups, there is a long tradition of examining primary bone microstructure to decipher growth rates and maturational timing, based on an empirical relationship between the microanatomy of primary bone and the rate at which it is deposited. We examined ontogenetic variation in primary bone microstructure at the midshaft femur of Chlorocebus aethiops, Hylobates lar, and Pan troglodytes to test whether tissue type proportions vary in accordance with predictions based on body mass growth patterns described previously. In all taxa, younger age classes were characterized by significantly higher percent areas of fibro-lamellar and/or parallel-fibered tissues, while older age classes showed significantly higher proportions of lamellar bone. In prior experimental studies, fibro-lamellar and parallel-fibered tissue types have been associated with faster depositional rates than lamellar bone. Principal components analysis revealed differences among taxa in the timing of this transition, and in the particular tissue types observed among individuals of similar dental emergence status. Among M1 and M2 age classes, higher proportions of parallel-fibered and fibro-lamellar tissues were observed in those taxa characterized by reportedly faster body mass growth rates. Further, persistence of fibro-lamellar tissue throughout DECID, M1 and M2 age classes in chimpanzees contrasts with the pattern reported previously for modern humans. Despite the necessary limitations of our cross-sectional study design and the secondary remodeling of bone in primates, large areas of primary bone remain intact and represent a valuable and independent source of information about the evolution of growth and development in the fossil record.